Diffusion Tensor Imaging and Decision Making in Cocaine Dependence - Lane, Scott D.; Steinberg, Joel L.; Ma, Liangsuo; Hasan, Khader M.; Kramer, Larry A.; Zuniga, Edward A.; Narayana, Ponnada A.; Moeller, Frederick Gerard (PloS one, 2010)
Chronic stimulant abuse is associated with both impairment in decision making and structural abnormalities in brain gray and white matter. Recent data suggest these structural abnormalities may be related to functional impairment in important behavioral processes. In 15 cocaine-dependent and 18 control subjects, we examined relationships between decision-making performance on the Iowa Gambling Task (IGT) and white matter integrity as measured by diffusion tensor imaging (DTI). Whole brain voxelwise analyses showed that, relative to controls, the cocaine group had lower fractional anisotropy (FA) and higher mean of the second and third eigenvalues (lambda perpendicular) in frontal and parietal white matter regions and the corpus callosum. Cocaine subjects showed worse performance on the IGT, notably over the last 40 trials. Importantly, FA and lambda perpendicular values in these regions showed a significant relationship with IGT performance on the last 40 trials. Compromised white matter integrity in cocaine dependence may be related to functional impairments in decision making.